ORIENTASI ENTREPRENEURSHIP DAN START UP DALAM UPAYA MENURUNKAN ANGKA PENGANGGURAN TERBUKA BAGI LULUSAN SMA/K DI KOTA BANJAR - Riza Purnama; Tina Cahya Mulyatin; Dara Siti Nurjanah; Dian Hadiani; Nova Chalimah Girsang (Universitas Perjuangan Tasikmalaya, 2024)
The problem of unemployment needs special attention from all parties, considering that currently the issue of population, namely the Demographic Bonus, has begun to be felt, where the number of productive ages is higher than other ages. This condition has an impact on the potential increase in the number of unemployed people in Indonesia, given the limited employment opportunities. This is also the case in Banjar City, where opportunities to get a job are limited while the number of labor force graduates from senior high school/K/MA each year is always increasing. The purpose of this Community Service is to increase the insight and motivation of participants through entrepreneurship orientation and business start-ups. The method used is a lecture by applying Case Based Method (CBM) based on case studies and realities and facts in the field, coupled with PreTest, Post Test instruments, and the existence of a Follow-up Plan (RTL) form. The results were quite significant, namely an increase in understanding and orientation to realize the start-up of participants who are graduates of SMA/K/MA in Kota Banjar who have not yet found a job. The conclusion of this activity is that everyone has the potential to start a business independently, but not everyone has the opportunity to do so, so encouragement and motivation are needed to make it happen.